2021
DOI: 10.1016/j.jad.2020.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Acute grief after deaths due to COVID-19, natural causes and unnatural causes: An empirical comparison

Abstract: Background: There are now over 800,000 registered deaths due to the COVID-19 pandemic worldwide. Researchers have suggested that COVID-19 death characteristics (e.g., intensive care admission, unexpected death) and circumstances (e.g., secondary stressors, social isolation) will precipitate a worldwide increase of prolonged grief disorder (PGD) and persistent complex bereavement disorder (PCBD). Yet, no study has investigated this. Since acute grief is a strong predictor of future pathological grief, we compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
169
7
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(191 citation statements)
references
References 8 publications
8
169
7
7
Order By: Relevance
“…The number is even six times more than that in Dutch citizens bereaved due to the Ukrainian plane disaster (6.6%) (30). While the prevalence of PCBD in our sample is higher than in previous studies, the symptom levels measured by the 18-item version of TGI-SR (57.39 ± 13.10) seems equivalent to that reported in a small group of Dutch people bereaved due to COVID-19 (57.37 ± 9.60) (26).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The number is even six times more than that in Dutch citizens bereaved due to the Ukrainian plane disaster (6.6%) (30). While the prevalence of PCBD in our sample is higher than in previous studies, the symptom levels measured by the 18-item version of TGI-SR (57.39 ± 13.10) seems equivalent to that reported in a small group of Dutch people bereaved due to COVID-19 (57.37 ± 9.60) (26).…”
Section: Discussioncontrasting
confidence: 67%
“…Despite the consensus that mental health professionals should pay attention to the rise of prolonged grief disorder after the COVID-19 pandemic (8,9) and call for evidence-based and culturally sensitive bereavement care for individuals bereaved during the pandemic (19)(20)(21)(22)(23)(24), no study speci cally focused on bereaved people and the impact that a death linked to a pandemic had on their subsequent grief before the COVID-19 (25). One recent empirical study included 49 Dutch individuals who experienced COVID-19 related bereavement showed that they reported more severe grief than people who experienced natural losses and equivalent levels of grief with people who experienced unnatural losses (26). Other than that, little is known about the prevalence, symptom severity, and associated factors of prolonged grief disorder among people whose close ones died from the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Certain segments of the population have done the heavy lifting when it comes to the risk of contracting the virus and working under highly pressurized conditions, including healthcare professionals, medical responders (e.g., ambulance drivers) and those in the critical infrastructure workforce (i.e., essential workers). Research on people in these professions/work roles, together with people bereaved by COVID-19 (Eisma et al, 2021), marginalized communities (Warren et al, 2020) and those who have existing mental illness (Asmundson et al, 2020), has shown dramatical elevations in levels of mental illness and PTSD (Buheji et al, 2020;Eisma et al, 2021;Groenewold et al, 2020;Shreffler et al, 2020;Skoda et al, 2020;Vindegaard & Benros, 2020). 2. seven of these studies have been conducted by authors in this paper or are related directly to a section below and are outlined in the coping, self-compassion, gratitude and positive emotions sections below.…”
Section: Notesmentioning
confidence: 99%
“…In keeping with this reasoning, recent research suggests that grief due to a COVID-19 death is indeed more severe than that resulting from other forms of loss, such as death through natural causes (Eisma et al, 2021). This finding is particularly concerning given that acute grief reactions in the early months of mourning is a risk factor for a protracted course of grief (Boelen & Lenferink, 2020;Bonanno et al, 1995;Bonanno & Keltner, 1997).…”
mentioning
confidence: 97%